Role of 18F-FDG PET/CT in the Assessment of Response to Antitubercular Chemotherapy and Identification of Treatment Endpoint in Patients With Tuberculosis of the Joints: A Pilot Study. (June 2021) - Goyal, Devansh; Shriwastav, Ravi; Mittal, Ravi; Sharma, Anshul; Sharma, Vijay; Kumar, Vijay D.; Sharma, M.C.; Kumar, Rakesh
Abstract : Aims: The aim of this study was to explore the utility of 18 F-FDG PET/CT in the assessment of response to antitubercular treatment (ATT) and identification of treatment endpoint. Patients and Methods: Forty patients (mean age, 35.3 years; 27 men) with clinically, radiologically, and histopathologically proven joint tuberculosis prospectively underwent clinical, biochemical, and PET/CT evaluation at baseline and after ~6, 12, and 18 months of ATT. Two patients were lost to follow-up, and 1 defaulted treatment. The remaining 37 were followed up until complete response (CR) was achieved. Images were visually and quantitatively (SUVmax ratio and metabolically active disease volume [MV]) evaluated by 2 experienced nuclear medicine physicians. Results: Knee (n = 18) and ankle (n = 7) were the most frequently involved sites. The median MV and SUVmax ratio at baseline were 85.10 mL and 7.21, respectively. Five patients had noncontiguous vertebral involvement, 12 had pulmonary lesions, 2 had abscesses, 6 had mediastinal, and 30 had local lymph nodal involvement. Complete response was seen in 1/39, 11/37, and 30/37 patients after 6, 12, and 18 months of ATT. Significant reductions in visual analog scale score, tenderness, joint swelling, SUVmax ratios, and MVs (Friedman test, P < 0.001) were seen after each follow-up. The median time-to-CR in skeletal lesions was significantly longer than extraskeletal lesions (591 vs 409 days; Wilcoxon signed-rank test, P < 0.001). Time-to-CR in joint lesions positively correlated with MV at first follow-up (Pearson = 0.452, P = 0.005) and negatively correlated with percentage change in MV (first follow-up from baseline) (Pearson = −0.620, P < 0.001). ROC analysis yielded a cutoff of ⩽71% reduction in MV at first follow-up (80.8% sensitivity, 81.8% specificity) to predict extension of ATT beyond 12 months. Using ROC analysis at second follow-up, a cutoff of ⩽12.67 mL (for CR) was derived and was validated in patients at the third follow-up, with an accuracy of 84.4%. Patients with CR in PET/CT maintained disease-free state during a mean follow-up of 271 days. Conclusions: 18 F-FDG PET/CT is an excellent tool in estimating total disease burden, assessing response to ATT and identification of treatment endpoint in joint tuberculosis.